2000
DOI: 10.1359/jbmr.2000.15.2.308
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Gene Polymorphism and Bone Loss: Estrogen Status Modifies the Influence of Apolipoprotein E on Bone Loss

Abstract: The identification of genes that contribute to bone mineral density (BMD) and bone loss has widespread implications for the understanding and prevention of osteoporosis. The objective of this study was to examine the relationship between the presence and absence of the apolipoprotein E*4 (APOE*4) allele and both BMD and annualized percentage rate of change in BMD at the lumbar spine and hip in a population of 392 healthy, pre-, peri-, and postmenopausal white women participating in the Women's Healthy Lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…In an Australian study of 940 postmenopausal women (≥70 years), Dick et al 14 found an association of APOE E4 with hip BMD. Interestingly, in a longitudinal study of 392 pre-, peri-, and postmenopausal women, Salamone et al 11 found no significant differences in baseline BMD at the spine or hip when comparing women with and without APOE E4 , but found that women having APOE E4 experienced significant bone loss over 2.5 years of follow-up compared with women without this allele. In addition, in a Korean study of 110 women with rheumatoid arthritis, Lee et al 15 reported a significant association of the APOE E4 allele with lumbar spine and femoral greater trochanter BMD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In an Australian study of 940 postmenopausal women (≥70 years), Dick et al 14 found an association of APOE E4 with hip BMD. Interestingly, in a longitudinal study of 392 pre-, peri-, and postmenopausal women, Salamone et al 11 found no significant differences in baseline BMD at the spine or hip when comparing women with and without APOE E4 , but found that women having APOE E4 experienced significant bone loss over 2.5 years of follow-up compared with women without this allele. In addition, in a Korean study of 110 women with rheumatoid arthritis, Lee et al 15 reported a significant association of the APOE E4 allele with lumbar spine and femoral greater trochanter BMD.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have reported cross-sectional and longitudinal associations between APOE E4 and BMD in the general population. 6 11 12 13 14 In 1997, Shiraki et al 6 first reported that BMD values were significantly reduced in APOE E4 carriers among 284 Japanese postmenopausal women. In the Longitudinal Aging Study Amsterdam of 519 participants (≥65 years), Pluijm et al 13 found that APOE E4 was associated with significantly lower femoral neck and trochanter BMD in women and was associated with hip BMD only in the 65–69-year-old age group in men.…”
Section: Discussionmentioning
confidence: 99%
“…[204][205][206][207] Several large studies that included males and females did not find an association of APOE genotype with bone mineral density (BMD). [208][209][210][211][212] However, targeted studies of postmenopausal woman find APOE4 carriers have lower BMD [213][214][215][216][217] or higher hip fracture risk, 218 although there have been null findings. 219 A meta-analysis found APOE4 to be associated with significantly lower BMD in trochanteric and lumbar spine, predominantly in females.…”
Section: Apoe Menopause and Htmentioning
confidence: 99%
“…220 Further, Salamone et al report that APOE4 is associated with lower BMD in peri-and postmenopausal women but not in premenopausal women. 216 Likewise, two studies find HT to be beneficial particularly among APOE4 carriers. 216,217 Collectively, available data support a modulatory role of APOE such that APOE4 appears to yield both greater vulnerability to and HT-mediated protection from menopause-related bone loss.…”
Section: Apoe Menopause and Htmentioning
confidence: 99%
See 1 more Smart Citation